Expression of nutrient transporter genes in response to dietary rice gluten meal and protease enzyme supplementation and the consequent effects on growth, nutrient digestibility, immunity and jejunum histomorphometry in chicken. Issue 7 (12th December 2022) - Wani, Manzoor A.; Tyagi, Pramod K.; Begum, Jubeda; Mir, Nasir Akbar; Dev, Kapil; Biswas, Avishek; Sharma, Divya; Goel, Akshat
Abstract: The objective of this study was to investigate the effects of feeding rice gluten meal (RGM) as an alternative protein source along with protease enzyme supplementation on growth performance, expression of nutrient transporter genes, nutrient digestibility, immune response and gut histomorphometry of broiler chicken. Proximate analysis of RGM revealed 923 g dry matter (DM), 500 g crude protein (CP), 69.2 g ether extract, 94.7 g crude fiber, 215.4 g nitrogen-free extract, 43.7 g ash, 6.20 g calcium, 7.80 g total phosphorus, 18.99 MJ gross energy and 12.68 MJ metabolizable energy per kg diet. Significant upregulation of nutrient transporter genes (PepT1, EAAT3 and mucin) and better growth performance was observed in the birds fed control diet which was statistically similar to the birds fed 150 g RGM compared to birds fed higher RGM levels. Histomorphometry of jejunum, nutrient digestibility, and immune response of birds did not reveal any significant effect of RGM or protease enzyme supplementation. However, the inclusion of RGM up to 150 g/kg diet resulted in significant decline of feed cost/kg live weight gain, dressed meat yield and eviscerated meat yield by 13.13%, 12.99% and 13.36%, respectively compared to control. Thus, it was concluded that the inclusion of 150 g RGM/kg diet in broiler chicken ration has no adverse effects on the growth pattern of birds and can be used for least-cost feed formulation for chicken.